Uncertainty-based comparison of conventional and surface topography-based methods for wear volume evaluation in pin-on-disc tribological test. (January 2022) - Maculotti, Giacomo; Goti, Edoardo; Genta, Gianfranco; Mazza, Luigi; Galetto, Maurizio
Abstract: Precise wear evaluation is essential to develop prediction models, applied to design materials, components and to optimise new manufacturing processes. Pin-on-disc is a widespread standardised conventional sliding wear test. Conventional characterisation of resulting wear exploits gravimetric or profilometric techniques. These have inadequate precision and accuracy for applications characterised by low-wear and uneven morphology and are being replaced with high-resolution and information-rich inspections to measure surface topography. Metrological characterisation of topography-based methods still lacks in literature, which prevents the performance comparison with conventional techniques. This paper develops a framework to evaluate topography-based methods' measurement uncertainty and compare methods' performances accordingly on experimental wear data on PTFE and Aluminium. Results show that topographic methods improve pin-on-disc characterisation's reliability. Highlights: Pin-on-disc is a well-established and widespread wear test for research purposes. Wear measurement standards do not include state-of-the-art topographical methods. Surface topography methods are exploited but lack uncertainty evaluation. Measurement uncertainty of topography-based wear measurement methods is formulated. A metrological approach compares standard and topographical method performances.